Non-pharmacological techniques to reduce pain and anxiety among parturients undergoing vaginal delivery: a systematic review (Research, Society and Development, 2022)
Objective: To analyze the main non-pharmacological techniques to reduce anxiety among parturients undergoing vaginal delivery. Methodology: This is a systematic review carried out using the PRISMA method, in the electronic databases PubMed, Scopus and Web of Science, using the following descriptors: “pregnancy”, “parturition”, “natural childbirth”, “anxiety”, “therapeutics” and “complementary therapies”. Full articles, available in Portuguese, English or Spanish, published between January 2016 and December 2021 and providing a detailed description of interventions to reduce anxiety in women undergoing vaginal delivery were included. Results: 11 articles made up the final sample of this study, with the highest frequency of publication in 2016 (n: 04) and greater production from Iran (n: 04) and Brazil (n: 03). All studies used the methodology of a randomized controlled clinical trial, characterizing the studies as presenting a strong level of evidence (II). The most used non-pharmacological techniques to reduce anxiety were: aromatherapy (n: 04), hydrotherapy with hot shower and perineal exercises with a ball (n: 02), music therapy (n: 02), breathing techniques (n: 02) and massage (n: 01). The periods of these interventions ranged from 10 minutes to 2 hours, most often lasting 30 minutes. Conclusion: Six non-pharmacological techniques were found to reduce anxiety in parturients undergoing vaginal delivery, with different effect sizes, especially aromatherapy and music therapy.